2020
DOI: 10.1039/c9ra08393f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the phenolic profiles and physicochemical properties of different varieties of thermally processed canned lychee pulp

Abstract: Lychee pulp is rich in phenolics and has a variety of biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…In this sense, TP managed to enhance the content and, consequently, bioaccessibility of these bioactive molecules up to 55% more, while both HHP treatments were capable of maintaining the initial flavanone content at a rather stable value compared with the untreated juice. This increase in flavonoids after thermal treatment may have been associated with the increased extractability of them as they were released when applying moderate temperatures during thermal treatment due to vegetable cell wall disruption, as previously reported [55,56]. It should be noted that the results of this study were in concordance with those found by He et al, who after thermal processing increased the total phenolic content up to 39% in orange juice, mainly due to the individual contribution of hesperetin-rutinoside, which increased its initial value by 27% post-pasteurization [57].…”
Section: Initial Impact Of Proccesing On the Overall Quality Parameters In Juicessupporting
confidence: 58%
“…In this sense, TP managed to enhance the content and, consequently, bioaccessibility of these bioactive molecules up to 55% more, while both HHP treatments were capable of maintaining the initial flavanone content at a rather stable value compared with the untreated juice. This increase in flavonoids after thermal treatment may have been associated with the increased extractability of them as they were released when applying moderate temperatures during thermal treatment due to vegetable cell wall disruption, as previously reported [55,56]. It should be noted that the results of this study were in concordance with those found by He et al, who after thermal processing increased the total phenolic content up to 39% in orange juice, mainly due to the individual contribution of hesperetin-rutinoside, which increased its initial value by 27% post-pasteurization [57].…”
Section: Initial Impact Of Proccesing On the Overall Quality Parameters In Juicessupporting
confidence: 58%
“…Su et al (2019) most obvious increase is the 121 • C treatment group of the Huaizhi variety, with procyanidin A2 content increasing nearly by five times, probably due to the oxidation of B-to A-type during processing (Su et al, 2019). Similar studies have demonstrated that the total phenolic content, procyanidin A2 content, and antioxidant activity of canned lychee can be improved by high-temperature treatment (Wang, Wu et al, 2020). It is also reported that open-air drying reduced the procyanidin A2 content of litchi peel by 30.5%, that hot-air oven drying above 40 • C degraded procyanidin A2 by nearly 51%, and that a combination of steam blanching and hot-air oven drying at 60 • C significantly increased the concentration of procyanidin A2 (p < .05) (Kessy et al, 2016).…”
Section: Heat Treatmentmentioning
confidence: 58%